Kant on phenomenal substance. - Spagnesi, Lorenzo (British Journal for the History of Philosophy, 2024)
In this paper, I offer a systematic account of Kant's view on 'phenomenal substance'. Several studies have recently analysed Kant's notion of substance. However, I submit that more needs to be said about how this notion is reconceptualized within the critical framework to vindicate a genuine and legitimate sense of substance in the phenomenal realm. More specifically, I show that Kant's transcendental idealism does not commit him to a rejection of substantiality in phenomena. Rather, Kant isolates a general notion of substance (as ultimate subject) and argues that (i) the relationality of phenomena is compatible with this notion; and that (ii) matter and all its parts are the ultimate subjects of everything existing in space (as what is independently movable in space). I suggest that vindicating a genuine and legitimate notion of phenomenal substance has far-ranging consequences for the interpretation of Kant's empirical realism.